2020
DOI: 10.4251/wjgo.v12.i10.1104
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of KIF23 expression in gastric cancer

Abstract: BACKGROUND Kinesin super family 23 (KIF23) is a member of the KIF family, and it plays an important role in mitosis and cytokinesis. Loss of expression can cause mitotic arrest. The Oncomine database is one of the largest oncogene chip databases in the world, and is an integrated data mining platform for cancer gene information. By querying the database, differences in expression between tumor tissue and normal tissue can be determined. AIM To study the expression and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…In this study, the expression level of KIF23 was high in GC tissues compared to that in adjacent normal tissues by several public databases. Recent studies suggested that KIF23 was highly expressed in GC (14,17), and related to its poor prognosis (17). Herein, we found that the pro le of KIF23 expression in GC tissue was consistent across different databases.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In this study, the expression level of KIF23 was high in GC tissues compared to that in adjacent normal tissues by several public databases. Recent studies suggested that KIF23 was highly expressed in GC (14,17), and related to its poor prognosis (17). Herein, we found that the pro le of KIF23 expression in GC tissue was consistent across different databases.…”
Section: Discussionsupporting
confidence: 58%
“…In lung adenocarcinoma, LINC00337 may up-regulate the expression of PBK and KIF23 through competitively binding to has-mir-373 and has-mir-519d (16). Although previous studies have con rmed the high expression of KIF23 in GC (17), the biology function and immune-related mechanism of KIF23 in mechanism remain unclear. Here, we comprehensively explored the expression and diagnostic value of KIF23, and its interactions with tumor-in ltrating immune cells (TIICs) using bioinformatics analysis.…”
Section: Introductionmentioning
confidence: 94%
“… 31 KIF23 promoted gastric carcinogenesis by activating Wnt/β-Catenin signaling. 32 , 33 Knockdown of KIF23 inhibited breast cancer cell proliferation and induced apoptosis. 34 Previous studies showed that DNA mutations in KIF23 can be found in half of cancer types with upregulated KIF23 expression and that CNAs of KIF23 are increased in 30% of tumors tested.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that elevated of KIF23 expression is a common event in various human cancers. KIF23 was reported to be overexpressed in pancreatic ductal adenocarcinoma ( Gao et al, 2020 ), malignant pleural mesothelioma ( Kato et al, 2016a ), lung cancer ( Kato et al, 2016b ; Ye et al, 2017 ), breast cancer ( Zou et al, 2014 ), hepatocellular carcinoma (HCC) ( Sun et al, 2015 ; Cheng et al, 2020 ), gastric cancer ( Li X. L. et al, 2019 ; Liang et al, 2020 ), and ovarian cancer ( Li T. et al, 2019 ; Hu et al, 2020 ). Interestingly, most studies also showed that patients with higher KIF23 expression had worse prognosis survival compared to these with lower KIF23 expression ( Kato et al, 2016b ; Ye et al, 2017 ; Li T. et al, 2019 ; Li X. L. et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%